PENGARUH KEPEMIMPINAN KEPALA SEKOLAH DAN MOTIVASI INTRINSIK TERHADAP KINERJA GURU DIMODERASI OLEH IKLIM ORGANISASIONAL (Studi Pada Guru PNS SMP Negeri Di Kecamatan Ulujami Kabupaten Pemalang) - Ida Yuliani, 1352020039; ., Sunarto (Jurnal Mahasiswa Pasca Sarjana, 2015)
This study was to investigate the effect of school leadership and intrinsic motivation on the performance of teachers with organizational climate is moderated. The specific objectives of the study was to examine and analyze the impact of school leadership on teacher performance, the influence of intrinsic motivation on teacher performance, the effects of climate organizational on teacher performance, whether climate organizational moderate the effects of school leadership on teacher performance, whether climate organizational moderating influence intrinsic motivation to teacher performance. This research is an explanatory research study that proves the effect of school leadership and intrinsic motivation on the performance of teachers with organizational climate moderated. This study uses the study population (census) amounted to 127 respondents. Data of this research is primary data obtained directly from the source. The method of data analysis using a model of moderation with a quasitype interaction techniques. The results showed that leadership principal does not affect the performance of teachers SMP Negeri in District Ulujami Pemalang; intrinsic motivation affect the performance of teachers SMP Negeri in District Ulujami Pemalang; organizational climate positive effect on teacher performance Ulujami of SMP Negeri in the District Pemalang; the organizational climate is not moderate the effects of school leadership on teacher performance Ulujami of SMP Negeri in the District Pemalang; organizational climate is not moderate the influence of intrinsic motivation on teacher performance Ulujami of SMP Negeri in the District Pemalang.Keywords: Principal Leadership, Intrinsic Motivation, Organizational Climate and Teachers Performance